Circular RNA circ_0026218 Suppressed Atherosclerosis Progression via miR-338-3p/SIRT6 Axis. (24th January 2023) - Yang, Liang; Chen, Wei; Li, Bin; Hu, Yvbao; Lu, Hua; Zhang, Pan; Yang, Huayun; Zhang, Mochen; Pan, Diguang
Abstract : Background . Multiple circular RNAs (circRNAs) are implicated in atherosclerosis (AS) pathogenesis. In fact, how circRNA 0026218 (circ_0026218) functions in AS remains unknown, and thus the functions and mechanisms of circ_0026218 in the injury of vascular endothelial cells are to be investigated. Methods . Microarray analysis was employed to screen out differentially expressed circRNAs in AS. A cell model was mimicked by treating Human umbilical vein endothelial cells (HUVECs) with oxidized low-density lipoprotein (ox-LDL). circ_0026218, microRNA-338-3p (miR-338-3p) and silent information regulator 6 (SIRT6) expressions in HUVECs with ox-LDL treatment were probed by qRT-PCR. The cell proliferative capabilities were exposed by CCK-8 assay. The contents of interleukin 6 (IL-6), interleukin 1 β (IL-1 β ), and tumor necrosis factor α (TNF- α ) were measured by ELISA. Oxidative stress kits were utilized to detect the levels of reactive oxygen species (ROS), superoxide dismutase (SOD), and malondialdehyde (MDA). Flow cytometry was adopted to analyze the level of apoptosis of HUVECs. Dual-luciferase reporter gene assay and RIP assay were leveraged to expose the interplay between miR-338-3p and circ_0026218 or SIRT6 3′ -UTR, respectively. In addition, the impacts of circ_0026216 and miR-338-3p on SIRT6 protein expressions were subjected to Western blot. Results . circ_0026218 was greatly depleted in ox-LDL-stimulated HUVECs. circ_0026218 overexpression promoted viability of HUVECs in vitro and inhibited inflammatory response, oxidative stress, and apoptosis. circ_0026218 could adsorb miR-338-3p and positively modulated SIRT6 expressions via sponging miR-338-3p. Upregulation of this miRNA reversed the influence of circ_0026218 overexpression on ox-LDL-caused injury and apoptosis of HUVECs. Conclusion . Collectively, circ_0026218 upregulates SIRT6 expression through decoying miR-338-3p, thereby inhibiting ox-LDL-initiated injury of HUVECs. circ_0026218 is involved in the pathogenesis of AS.